1996
DOI: 10.1101/gad.10.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that sequence-independent binding of highly conserved U2 snRNP proteins upstream of the branch site is required for assembly of spliceosomal complex A.

Abstract: A critical step in the pre-mRNA splicing reaction is the stable binding of U2 snRNP to the branchpoint sequence (BPS) to form the A complex. The multimeric U2 snRNP protein complexes SF3a and SF3b are required for A complex assembly, but their specific roles in this process are not known. Saccharomyces cerevisiae homologs of all of the SF3a, but none of the SF3b, subunits have been identified. Here we report the isolation of a cDNA encoding the mammalian SF3b subunit SAP 145 and the identification of its proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
263
2
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(292 citation statements)
references
References 27 publications
20
263
2
4
Order By: Relevance
“…Previous studies have indicated that the RES complex contacts U2 snRNP proteins 4,12 , suggesting that it might bind to the pre-mRNA in the vicinity of U2. In human spliceosomes, most U2 snRNP proteins bind to a region directly upstream of the branch site 29 , whereas in yeast only one U2 snRNP protein, Hsh155p, interacts with pre-mRNA between the branch point and the 3′ splice site 30 . To test a possibility of Snu17p interacting in this region we assembled B act∆prp2 complexes on site-specifically labeled pre-mRNAs that carried a single 32 P label directly 3′ of G nucleotides downstream of the branch site (Fig.…”
Section: Npg a R T I C L E Smentioning
confidence: 99%
“…Previous studies have indicated that the RES complex contacts U2 snRNP proteins 4,12 , suggesting that it might bind to the pre-mRNA in the vicinity of U2. In human spliceosomes, most U2 snRNP proteins bind to a region directly upstream of the branch site 29 , whereas in yeast only one U2 snRNP protein, Hsh155p, interacts with pre-mRNA between the branch point and the 3′ splice site 30 . To test a possibility of Snu17p interacting in this region we assembled B act∆prp2 complexes on site-specifically labeled pre-mRNAs that carried a single 32 P label directly 3′ of G nucleotides downstream of the branch site (Fig.…”
Section: Npg a R T I C L E Smentioning
confidence: 99%
“…Human SF3 is involved in binding of U2 snRNP to the branch site in the splicing reaction+ The interaction between each of the SF3 subunits and the pre-mRNA sequences around the branch point sequence was analyzed by the UV-crosslink assay (Gozani et al+, 1996)+ SF3 subunits except for SAP130/SF3b130 crosslinked with the nucleotides at the 59-side of the branch site called an anchoring site+ SAP130/SF3b130 did not bind to pre-mRNA directly (Gozani et al+, 1996)+ Therefore, it is possible that SAP130/Prp12p has a role different from those of other SF3 subunits, although the exact function of each SAP in pre-mRNA splicing is still unknown+ An interesting phenotype of prp12-1 is a substratespecific splicing defect at the nonpermissive temperature+ In the analyzed pre-mRNAs, only TfIId ϩ pre-mRNA showed splicing defects at the nonpermissive temperature+ As we detected a small amount of unspliced TfIId ϩ pre-mRNA even in the wild-type cells (Fig+ 6A), TfIId ϩ pre-mRNA appears to be a substrate with low splicing efficiency in vivo+ Thus, one explanation for the substrate-specific splicing defect in prp12-1 is that mutated Prp12p produced from the prp12-1 allele retains residual activity even at the nonpermissive temperature, which does not affect splicing of efficiently spliced transcripts but does cause splicing inhibition in "poor" splicing substrates, such as TfIId ϩ FIGURE 5. A: Cytological analysis of prp12-1.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether this protection is established prior or subsequent to exon ligation, we now report RNase H analysis of two pre-mRNAs that accumulate splicing intermediates. One RNA derived from the standard AdML splicing substrate (AdML-AG), but contains an AG → GG mutation at the 3Ј splice site (AdML-GG; Gozani et al 1996;Anderson and Moore 1997). The other (␣-TM) derived from E2-I2-E3 of rat ␣-tropomyosin (Smith et al 1989) and was truncated upstream of the 3Ј splice site.…”
Section: Extensive Rnase Protection Of the 5ј Exon Intermediatementioning
confidence: 99%